The use of the interactive digital whiteboard in the teaching-learning process in Higher Education (Educational Knowledge, 2015)
Regarding information and communication technologies (ICTs), there is a variety of resources that can potentially be used to make the teaching and learning process more dynamic and engaging. The interactive whiteboard (IWB) is a relatively new option in the educational context, and there is a wide variety available: touch-sensitive digital whiteboards with a grid; electromagnetic digital whiteboards with a stylus; touch-sensitive digital whiteboards using infrared; and ultrasonic-infrared digital whiteboards with a stylus. This last type was studied for its functionality as a teaching resource, as well as its implementation in the development of methodologies that promote pedagogical innovation. Quantitative and qualitative aspects were also examined to visualize students' academic performance. For this purpose, an evaluative case study was used as the research methodology.
Keywords: Interactive-digital board; technology; innovation; Methodology